Comprehensive technological assessment for different treatment methods of leather tannery wastewater - Nigam M.; Mishra P.; Kumar P.; Rajoriya S.; Pathak P.; Singh S.R.; Kumar S.; Singh L. (My University, 2025)
Abstract: The leather-making process necessitates large amounts of water and consequently generates tons of liquid waste as leather tannery wastewater (TWW) is disposed of directly in the open environment. Open disposal of untreated TWW into the natural environment causes an accumulation of various polluting compounds, including heavy metals, dyes, suspended solids inorganic matter, biocides, oils, tannins, and other toxic chemicals. It thus poses potential hazards to the environment and human health. This study primarily focuses on providing in-depth insight into the characteristics, treatment strategies, and regulatory frameworks for managing TWW in leather processing industries. Different technologies of conventional physico-chemical (equalization, coagulation, and adsorption), advanced approaches (Fenton oxidation, ozonation, cavitation), thermo-catalytic and biological treatments available to treat TWW, and their integrative approaches were also highlighted. This review also sheds light on the most frequently applied technologies to reduce contaminant load from TWW though there are several limitations associated with it such as being ineffective for large quantities of TWW, waste generation during treatment, and high operational and maintenance (O&M) costs. It is concluded that the sustainable alternatives applied in the current TWW technologies can minimize O&M costs and recirculate the treated water in the environment. The exhaustive observations and recommendations presented in this article are helpful in the industry to manage TWW and recirculate the water in a sustainable manner. Graphical abstract: [Figure not available: see fulltext.] © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.